[Farmers struggle ; Dangerous obsessions ; Life on the cat walk [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
A report on the social conditions of victims of Mayon volcano eruption and anorexia and bulemia nervosa striking the upper class society especially young Filipino women. Model Tweety de Leon and her frieds talk about the fashion modeling.